A new approach to fluid management in diabetic ketoacidosis. (29th September 2015) - Panjwani, D; Wilkinson, J; Weerasinghe, K
Abstract : Diabetic fetoacidosis (DKA) is an emergency requiring adequate fluid resuscitation. This can be high risk owing to multiple calculations, the need for addition of potassium containing fluids in clinical areas (a practice no longer recommended) and delays in administration of fluids. A new protocol was introduced in our hospital in March 2007. The co-administration, at independently controlled rates, of two separate infusions: an in-house pharmacy prepared potassium infusion, and an appropriate crystalloid infusion, was used to control the concentration of glucose and electrolytes administered. An algorithm was developed to reduce error involved in the calculation process. Aims: The authors intend to determine the efficacy of the new protocol introduced in our hospital in comparison to our previous practice. Methods: This is a retrospective case note based study. A list of consecutive patients who presented with DKA between January 2003 and May 2009 was obtained. Case notes were reviewed and data collected using a proforma. Assimilated data were analysed to obtain an objective difference between the old and new regimes. Results: A total of 30 patients were identified. 13 managed using the old regime and 17 with the new regime. Of patients using the old regime, 8% required up to 80 mmol/l of potassium compared to 6% in the new regime. It was also noticed that changes in the rate of potassium infusion was 41% with the current practice vs 85% in the old regime. Accuracy of rehydration fluid calculation increased from 31% to 94% with the new protocol. Interestingly fluids were changed less frequently with the current protocol (41% vs 85%). The number of days of stay in hospital for known diabetic patients averaged 3.1 on the old regime and 2.7 on the new regime. Conclusions: The current protocol allows fast and flexible dose adjustment of potassium containing crystalloid solutions with demonstrable improvement to the accuracy of rehydration fluid calculation. The protocol improves both the safety of administration of fluids and accurate control of glucose and potassium. The average number of days in hospital is less for patients on the new protocol thereby implying cost reductions.